Who Is a Muslim? : Orientalism and Literary Populisms - Khan, Maryam Wasif (Book collections on Project MUSE., 2021)
Who is a Muslim? destabilizes traditional constructions of postcolonial literary histories through the specific example of Urdu by suggesting that this North-India vernacular, far from secular or progressive, has been shaped as the authority designate around the intertwined questions of piety, national identity, and citizenship.